Analysis Of The Credibility Of Utilizing Brand Ambassador To Compete Between Shopee And Tokopedia Using Social Network Analysis On Twitter - Anjani, Syafina Putri; Ambarwati, Rita (Jurnal Manajemen, 2023)
Human life has become more practical with the internet. Nowa-days, people prefer to shop online on marketplaces. The market-places that are widely used by Indonesians are Shopee and To-kopedia. Shopee invites Blackpink and stray kids to become brand ambassadors, while Tokopedia invites BTS. Involving celebrities in promoting and marketing a product or service is a phenomenon currently widely used by companies to attract consumer attention and increase sales. Brand Ambassador is someone who is used by a company to attract attention or influence consumers because they are considered to be able to persuade consumers to buy products or use these services. In addition, brand ambassadors also influence potential consumers in making decisions to buy these products. The purpose of this research is to find out whether, by using the SNA method, it can be seen that the marketplace us-ing brand ambassadors can be known by the wider community. This type of research is qualitative, and the data sources collected are secondary. This study uses the SNA (Social Network Analysis) method. The results of the research after data visualization showed that there was quite a lot of interaction between Twitter users who talked about the Blackpink brand ambassadors, stray kids at Shopee, and BTS at Tokopedia. This makes this market-place widely known by many people.